MR Imaging Scoring System for White Matter Injury after Deep Medullary Vein Thrombosis and Infarction in Neonates - Benninger, K.L. (AJNR Am J Neuroradiol, 2019)
BACKGROUND AND PURPOSE: Advanced imaging techniques have allowed earlier and more accurate detection of cerebral deep medullary vein thrombosis and infarction. Our objective was to develop an MR imaging scoring system to evaluate the severity of white matter injury in neonates with deep medullary vein thrombosis and infarction. MATERIALS AND METHODS: This was a retrospective study of infants born ≥32 weeks' gestation (2000–2016) diagnosed with deep medullary vein thrombosis and infarction on neuroimaging in the first 30 days of life. A 102-point deep medullary vein white matter injury global severity score was developed. MR images were scored by 2 pediatric radiologists. Subject clinical data and regional and global severity scores were recorded. RESULTS: Fifty-one patients (mean gestational age, 37.3 ± 2.2 weeks; mean birth weight, 3182 ± 720 g) were included with a mean age at diagnosis via MR imaging of postnatal day 10.1 ± 6.1. Global severity scores ranged from 1 to 53, with a median score of 11 (interquartile range, 5–25). Lesions were more common in the frontal and parietal regions and less common in the occipital and temporal regions. Fifty-five percent of the group had neonatal seizures. No difference in perinatal risk factors (gestational age, birthweight, 5-minute Apgar score, chorioamnionitis, delivery room resuscitation, ventilator, or inotrope requirement) was observed among severity score quartiles. CONCLUSIONS: An MR imaging scoring system provides a comprehensive and objective classification of WM injury after deep medullary vein thrombosis and infarction in late preterm and term neonates. The global severity score is independent of gestational age and other antenatal risk factors, consistent with presentation in previously healthy-appearing neonates.